2012
DOI: 10.1029/2011jd016504
|View full text |Cite
|
Sign up to set email alerts
|

Summertime formaldehyde observations in New York City: Ambient levels, sources and its contribution to HOx radicals

Abstract: [1] Measurements of ambient formaldehyde (HCHO), related gases and particulate matter were carried out from the SUNY Albany mobile platform at the Queens College site in New York City (NYC) from 15 July to 3 August 2009. Ambient HCHO was measured using a quantum cascade laser (QCL) trace gas detector. HCHO concentrations ranged from 0.4 to 7.5 ppb with a mean value of 2.2 AE 1.1 ppb. Daily HCHO peaks were nearly always found between 1100 EST (Eastern Standard Time) and noontime throughout the sampling period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 85 publications
3
53
0
Order By: Relevance
“…Given the short lifetime of HCHO (typically 3-4 h during the summertime conditions), the continuous increase of HCHO till 14:00 suggests that aerosol processing during the early stage III was most likely driven by local photochemical oxidation. The decrease of HCHO after 14:00 was likely due to photolysis and further oxidation by OH (Lin et al, 2011), consistent with the oxidation of SV-OOA to LV-OOA in the afternoon. LV-OOA + SV-OOA, a surrogate of SOA, shows tight correlation with O 3 (r 2 = 0.84) but weaker correlation (r 2 = 0.40) with O x (NO 2 + O 3 ), likely due to an important contribution of NO 2 from local emissions.…”
Section: Photochemical Production Of Soamentioning
confidence: 63%
See 2 more Smart Citations
“…Given the short lifetime of HCHO (typically 3-4 h during the summertime conditions), the continuous increase of HCHO till 14:00 suggests that aerosol processing during the early stage III was most likely driven by local photochemical oxidation. The decrease of HCHO after 14:00 was likely due to photolysis and further oxidation by OH (Lin et al, 2011), consistent with the oxidation of SV-OOA to LV-OOA in the afternoon. LV-OOA + SV-OOA, a surrogate of SOA, shows tight correlation with O 3 (r 2 = 0.84) but weaker correlation (r 2 = 0.40) with O x (NO 2 + O 3 ), likely due to an important contribution of NO 2 from local emissions.…”
Section: Photochemical Production Of Soamentioning
confidence: 63%
“…1c). Detailed analysis of the sources of HCHO during this campaign showed that on average ∼60 % of HCHO was produced from photochemical reactions, mainly oxidation of isoprene, methane, and propene (Lin et al, 2011). Given the short lifetime of HCHO (typically 3-4 h during the summertime conditions), the continuous increase of HCHO till 14:00 suggests that aerosol processing during the early stage III was most likely driven by local photochemical oxidation.…”
Section: Photochemical Production Of Soamentioning
confidence: 99%
See 1 more Smart Citation
“…The ratios of HCHO/acetaldehyde can be used as an indicator to perform a diagnostic evaluation, qualitatively, on the biogenic/anthropogenic origins of HCHO [2]. Several methods were used to quantify the primary and secondary sources of HCHO, such as methods based on the emission ratios of HCHO/tracer of primary sources [3,4], the multi-linear regression method based on ambient measurements of HCHO and tracers [5,6], the photochemical age method based on parameterization of atmospheric reactions [7,8] and receptor models like positive matrix factorization (PMF) [9,10]. In this study, the multi-linear regression approach was selected to estimate the HCHO sources in Ziyang city.…”
Section: Introductionmentioning
confidence: 99%
“…HCHO is one of the most prevalent VOCs in the Earth's atmosphere. It can be produced by the photooxidation of most VOCs and serve as an important source of HO x radical (Lin et al, 2012), peroxy radicals, and peroxyacyl nitrates (Carlos-Cuellar et al, 2003). Therefore, its dual role makes it as an important species for testing the performance of photochemical oxidant models.…”
Section: Introductionmentioning
confidence: 99%